Turk Arch Pediatrics 2023
DOI: 10.5152/turkarchpediatr.2021.21090
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination in Children With Ongoing Cancer Treatment: A Safety and Efficacy Study of Super-Accelerated Vaccination Scheme

Abstract: Objective: Children with cancer have an increased risk for hepatitis B virus (HBV) infections due to chemotherapy-induced secondary immunodeficiency and frequent blood transfusions. The aim of this study is to evaluate the efficacy and safety of hepatitis B vaccination during the intensive induction chemotherapy in children with cancer found to be seronegative for hepatitis B on admission. Materials and Methods: Children newly diagnosed with cancer were evaluated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Toret et al 13 found that 39% of leukemia patients had hepatitis A seronegativity before treatment, which increased to 83% 6 months after the cessation of therapy. Immunization of hepatitis A and B seronegative children with cancer before or during therapy is well-established in terms of safety and efficacy 14,15 . Yetgin and colleagues studied hepatitis B seroprevalence in children with leukemia based on the status and timing of HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toret et al 13 found that 39% of leukemia patients had hepatitis A seronegativity before treatment, which increased to 83% 6 months after the cessation of therapy. Immunization of hepatitis A and B seronegative children with cancer before or during therapy is well-established in terms of safety and efficacy 14,15 . Yetgin and colleagues studied hepatitis B seroprevalence in children with leukemia based on the status and timing of HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization of hepatitis A and B seronegative children with cancer before or during therapy is well-established in terms of safety and efficacy. 14,15 Yetgin and colleagues studied hepatitis B seroprevalence in children with leukemia based on the status and timing of HBV vaccination. They discovered that children vaccinated prior to diagnosis had the lowest percentage of HBV infection, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization, an essential approach to bolster immune function and reduce infections, also plays a significant role in enhancing the prognosis of immune levels in children with tumors ( 28 , 29 ). Research has demonstrated a low occurrence of adverse reactions among vaccinated children ( 30 ), including those diagnosed with neuroblastoma ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%